The Exodus case a scientific examination of the Exodus story - and a deep look into the Red Sea - Moller, Lennart; Wyatt, Ronald E.; Mikkelsen, Anni; Montero, Jose Perez; Backman, Margaret (Copenhagen, Denmark Scandinavia Publishing House, 2000)
Includes bibliographical references, index, photographs, maps, illustrations.
Keywords: Bible. O.T. Exodus -- history of contemporary events